30‐2: High Refractive Index Glass Wafers for Augmented Reality: Boundary Conditions for an Excellent Optical Performance. Issue 1 (28th June 2021) - Bachhuber, Frederik; Sprengard, Ruediger; Thomas, Jens Ulrich; Damm, Thorsten; Weidlich, Stefan; Nass, Peter; Ottermann, Clemens; Plapper, Volker; Fang, Helen; Weng, Nicolas; Wang, Alex
Abstract : Planar, high refractive glass wafers are the backbone of leading Augmented/Mixed Reality devices. They route the virtual image to the user's eye, while helping to keep the form factor small. While the glass characteristic directly affects fundamental design parameters like Field‐of‐View, the optical system of the wafer with its surfaces and interfaces as a whole determines the image quality. Besides surface quality of the glass itself, the adjacent coatings, such as anti‐reflective coating and polymer coating with a grid structure can significantly contribute to the total optical loss. Here we are reporting on optical losses caused by surface effects and polymer coatings that might lead to disadvantages in key quality parameters, such as contrast, brightness and distortion of the image.